INDUSTRY-RESPONSIVE AND ISLAMIC CURRICULUM: A NEEDS ANALYSIS FOR PUBLIC VOCATIONAL SECONDARY SCHOOLS - Rhafiiqul Azhari Karim; Ahmad Rifki; Nadir; Dori Rusyunizal; Liza Efriyanti (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2025)
This study aims to analyze the needs of a curriculum that is responsive to the industry as well as relevant to Islamic values at SMKN 4 Payakumbuh majoring in Informatics Engineering. The current vocational curriculum faces the challenge of aligning technical competencies with the demands of the digital industry without neglecting the moral and character aspects of students. Using a qualitative approach through interviews, questionnaires, and focus group discussions, this research explores the perspectives of vocational teachers, industry players, students, and Islamic education leaders. The results show the need for curriculum reformulation that not only emphasizes mastery of skills such as programming, computer networking, and multimedia design, but also the integration of Islamic ethical values in the learning process. The strength of the current curriculum lies in its adaptability to technology and the industrial world, but there are still weaknesses such as limited infrastructure, lack of teacher training, and lack of integration of subjects across disciplines. Therefore, the proposed curriculum model is expected to bridge the gap between the world of education and the world of work while maintaining the moral identity of students. Keywords: Vocational Curriculum; Industry 4.0; Islamic Values.   Abstrak Penelitian ini bertujuan untuk menganalisis kebutuhan kurikulum yang responsif terhadap industri sekaligus relevan dengan nilai-nilai Islam di SMKN 4 Payakumbuh jurusan Teknik Informatika. Kurikulum kejuruan saat ini menghadapi tantangan untuk menyelaraskan kompetensi teknis dengan tuntutan industri digital tanpa mengabaikan aspek moral dan karakter peserta didik. Dengan menggunakan pendekatan kualitatif melalui wawancara, kuesioner, dan diskusi kelompok terfokus, penelitian ini menggali perspektif dari guru kejuruan, pelaku industri, siswa, dan tokoh pendidikan Islam. Hasilnya menunjukkan perlunya reformulasi kurikulum yang tidak hanya menekankan penguasaan keterampilan seperti pemrograman, jaringan komputer, dan desain multimedia, tetapi juga integrasi nilai-nilai etika Islam dalam proses pembelajaran. Kekuatan kurikulum saat ini terletak pada adaptabilitasnya terhadap teknologi dan dunia industri, namun masih ditemukan kelemahan seperti keterbatasan infrastruktur, minimnya pelatihan guru, dan kurangnya integrasi mata pelajaran lintas disiplin. Oleh karena itu, model kurikulum yang diusulkan diharapkan dapat menjembatani kesenjangan antara dunia pendidikan dan dunia kerja dengan tetap menjaga identitas moral peserta didik. Kata kunci: Kurukulum Kejuruan; Industri 4.0; Nilai-Nilai Islam.